Recoverability and Expectations-Driven Fluctuations - Chahrour, Ryan; Jurado, Kyle (Review of Economic Studies, 2022)
Abstract Time series methods for identifying structural economic disturbances often require disturbances to satisfy technical conditions that can be inconsistent with economic theory. We propose replacing these conditions with a less restrictive condition called recoverability, which only requires that the disturbances can be inferred from the observable variables. As an application, we show how shifting attention to recoverability makes it possible to construct new identifying restrictions for technological and expectational disturbances. In a vector autoregressive example using post-war U.S. data, these restrictions imply that independent disturbances to expectations about future technology are a major driver of business cycles.